Self-control in old age: A grounded theory study - Laarni A. Caorong (Belitung Nursing Journal, 2021)
Background: Self-control is associated with multiple positive outcomes. There are several studies on self-control, yet no literature describing the mechanism of self-control in old age. Objective: This study aims to develop a substantive theory on the exercise of self-control in old age. Methods: Grounded Theory methodology developed by Glaser & Strauss was utilized in the conduct of this study with ten (10) older adults as participants following the set of inclusion and exclusion criteria. Individual in-depth interviews of 30-45 minutes were observed to gather the needed verbatim narrative responses from each participant after careful consideration of the ethical procedures approved by the University research ethics board. Major themes with their respective sub-themes were generated after rigorous analysis of the participants’ responses following the steps provided by Glasser & Strauss in conducting grounded theory studies. Results: This study resulted in the formulation of three propositions such as: (1) Older adults exercise self-control differently, (2) several personal motivations are involved in the exercise of self-control, and (3) the exercise of self-control leads to life satisfaction. From the propositions emerged the Theory of Self-control in Old age, which states that the process of self-control encompasses the human capability of exercising self-restraint to overrun different types of desires, passions, and temptations. The theory posits that older adults vary in their exercise of self-control depending upon their personal motivations. The theory also assumes that the exercise of self-control results in life satisfaction as displaying self-control is attributed to a host of positive life outcomes. Conclusion: The present study has important implications in the field of gerontology and health care services since the older population is growing, and so does the demand for health care services. The need to understand the choices and decisions of older adult clients is fundamental in individualizing the health care services that may be designed and provided for them.